Revitalizing ‘Urf in State Legal Development: The Case of Minangkabaunese Marriage Traditions - Zulkifli, Zulkifli; Zikri, Ahmad; Artiningsih, Dwi Wahyu; Zainuddin, Zainuddin; Helim, Abdul (AL-ISTINBATH : Jurnal Hukum Islam, 2024)
This article aims at explaining the marriage regulations in several Minangkabau regions which contribute to the enforcement and development of state law. These marriage rules have become a tradition that must be obeyed by the Minangkabaunese and recognized by Sharia, which in this case is categorized as ‘urf shahih. This research was conducted by using qualitative method. It was done by inventorying several marriage rules that are still applied by the Minangkabaunese and recognized by Sharia. The data were analyzed for their conformity with the provisions of marriage law established by the state. This research found that several forms of regulations are still applied and contribute to the development and enforcement of state law such as traditions before marriage, the process of getting married and living in the household, as well as when problems arise in the household and divorce. This ‘urf needs to be re-actualized to achieve good state law enforcement. This research confirms the need for the state to consider local traditions (‘urf) in developing and enforcing laws.